2022
DOI: 10.1111/desc.13262
|View full text |Cite
|
Sign up to set email alerts
|

Development of upper visual field bias for faces in infants

Abstract: The spatial location of the face and body seen in daily life influences human perception and recognition. This contextual effect of spatial locations suggests that daily experience affects how humans visually process the face and body. However, it remains unclear whether this effect is caused by experience, or innate neural pathways. To address this issue, we examined the development of visual field asymmetry for face processing, in which faces in the upper visual field were processed preferentially compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…They showed that the VMA is a malleable property of the visual system that settles in beyond childhood. Another recent study concluded that perceptual asymmetries in infants reflect adaptations to typical spatial locations in the surrounding environment 28 . With regards to aging, data pertaining to upper-lower asymmetries are scarce and they remain largely inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the VMA is a malleable property of the visual system that settles in beyond childhood. Another recent study concluded that perceptual asymmetries in infants reflect adaptations to typical spatial locations in the surrounding environment 28 . With regards to aging, data pertaining to upper-lower asymmetries are scarce and they remain largely inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Daylight-axis colors are important for object recognition and segmentation (Gegenfurtner and Rieger, 2000;Lafer-Sousa et al, 2012;Pearce et al, 2014;Rosenthal et al, 2018), and responses to daylight colors appear to distinguish ventral and dorsal parcels, particularly in V3 and V4 (Figure 5b). A potential behavioral advantage for color-in-service-of-object-vision in the upper visual field may parallel the behavioral advantage in the upper visual field found for face perception Finkbeiner, 2014, 2015;Tsurumi et al, 2022) and shape perception (Zito et al, 2016) in the upper visual field.…”
Section: The Origin Of Dorsal / Ventral Functional Asymmetriesmentioning
confidence: 83%
“…That is, adults direct their visual attention toward the top half of the stimuli and not to a specific facial feature (Barton et al., 2006; Man & Hills, 2016), whereas infants have been shown to focus on the eye region regardless of stimulus orientation (Oakes & Ellis, 2013). However, recent findings show a general looking preference toward the upper visual field compared to the lower visual field in infants (Tsurumi et al., 2023), which may explain the differences in first fixation location between upright and inverted faces. Moreover, previous work with adults shows that the location of the first fixation is predictive of recognition accuracy, with best recognition performance when the first fixation is directed to the eyes (Hills et al., 2013a).…”
Section: Discussionmentioning
confidence: 94%